Comparative Study of the Structures of French and Yoruba Idiomatic Expressions - Fabiyi, Eunice Modupe (NIU Journal of Humanities, 2023)
Yoruba and French languages are so rich in the use of idiomatic expressions which lend themselves easily in the hands of those who know the two languages, through limitless improvisation of idiomatic expressions. In friendly, family and societal conversations, idiomatic expressions occupy a unique place. Their importance cannot be over emphasized as they add beauty to the speeches that employ them and provide knowledge and wisdom for better and clear understanding of the messages being projected. This paper therefore, examines idiomatic expressions in both languages at different fora. The paper hinges on Cognitive Linguistics which claims that idiomatic expression, which is motivated by metaphor, is not merely a figure of speech, but a specific mental and neutral mapping that influences a good deal of how people think, reason and imagine in everyday life. It was complemented with Conceptual Metaphor Theory which postulates that human thought process are largely metaphorical, and human conceptual system is structured and defined in a metaphorical way.  The examples of  Yoruba idiomatic expressions used in the paper were taken from two authentic Yoruba text books; Yoruba idioms by M.A. Fabunmi and Asayan Akanlo Ede Yoruba by Ademola Olopade while French idiomatic expressions were taken from Dictionnaire Des Expressions Et Locutions, second edition by Allain Ray et Sophie Chantreau. Our findings reveal that, the idiomatic expressions in both languages have similar characteristics, similar functions and at times have mutual equivalence. Also idioms in both languages can have the same word patterns but different lexical items due to different cultures.   Keywords:   Yoruba, French, idiomatic expressions, cognitive linguistics, conceptual metaphor theory.